2001
DOI: 10.1007/s10434-001-0116-3
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Plasma Cytokine Levels in Melanoma Patients With Histologically Negative Sentinel Lymph Nodes

Abstract: Among melanoma patients with clinically localized disease who have undergone a histologically negative SLN biopsy, presence of a detectable plasma level of IFN-gamma is an independent predictor of disease recurrence. Elevated levels of IFN-gamma may identify a group of early-stage melanoma patients who are more likely to have recurrence of disease and who may benefit from adjuvant therapies, including immunotherapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 32 publications
3
16
1
Order By: Relevance
“…In general, these results are consistent with studies of others that have revealed Th2 cytokine skewing in cancer patients [17]. For example, serum IL-6 levels have been demonstrated to correlate with disease status of gastric cancer, although whether there was a concurrent decrease in Th1 cytokines was not determined [18].…”
Section: Discussionsupporting
confidence: 92%
“…In general, these results are consistent with studies of others that have revealed Th2 cytokine skewing in cancer patients [17]. For example, serum IL-6 levels have been demonstrated to correlate with disease status of gastric cancer, although whether there was a concurrent decrease in Th1 cytokines was not determined [18].…”
Section: Discussionsupporting
confidence: 92%
“…Activation of macrophages is also produced by cytokines released by stimulated lymphocytes, and IFN-␥ has been shown to activate macrophages to become tumoricidal (38). However, in this study, IFN-␥ in the regional lymph node did not increase after cancer cell inoculation or NAAI pretreatment for macrophage activation, and an inadequate IFN-␥ response is also found in the sentinel lymph node of melanoma-bearing patients (39). IL-12 has been found to enhance IFN-␥ production and activate T cells, resulting in tumor growth inhibition (40), but in the present study, IL-12 did not up-regulate IFN-␥ after cancer cell inoculation.…”
Section: Discussioncontrasting
confidence: 71%
“…In support of these findings, distinct aggressive tumor phenotypes expressing high IFN-γ predict poor patient survival (27). Also, elevated serum IFN-γ predicted cancer recurrence and reduced disease-free survival in melanoma patients (28). Because INF-γ up-regulates NOS2 in aggressive breast cancer cells, we explored potential mechanistic effects linking IFN-γ signaling with elevated NOS2 tumor expression that predicted poor breast cancer specific survival in ER − patients (4).…”
Section: Discussionmentioning
confidence: 97%